COVID-19 Pandemic and Compassionate Leadership: Lessons Learned from Woman in Local Governance - Andi Tenri Sompa; Abdillah Abdillah; Zahra Ahmadi (Journal of Contemporary Governance and Public Policy, 2023)
This study aims to explore the leadership of Indah Putri Indriani as a regent within the North Luwu Regency Government in the process of compassionate leadership in facing the challenges of the Corona Virus Disease 2019 (COVID-19) in North Luwu Regency. This research method is exploratory-qualitative with a phenomenological approach in exploring the process of compassionate leadership in facing the threat of the COVID-19 pandemic in North Luwu Regency. The results of this study indicate that the COVID-19 pandemic in the North Luwu Regency highlights the need for leaders to apply the principle of compassion in order to be able to make decisions and programmes that encourage integrated and appropriate cross-sectoral responses, taking into account contextual factors in their implementation. In handling the Corona Virus Disease 2019, the government of North Luwu Regency created a cooperation programme with UNICEF Indonesia and Geneva Madani in North Luwu Regency. Then, from these two programs, create a home medicine budget allocation programme for people affected by the Corona Virus Disease 2019 in North Luwu Regency, highlighting the reduction of suffering and difficulties for local people in North Luwu Regency. This research contributes to providing knowledge about lessons learned from local governments dealing with difficult situations such as the Corona Virus Disease of 2019 by prioritising the mindset and attitude of compassionate leadership. This approach emphasises a better understanding of the real needs and difficulties faced by the community.